Mathematical model to determine the Coagulation Time Human Blood from Experimental Data (2015)
In this paper a linear mathematical model of first order with delay is presented to characterize the clotting time of blood from experimental data obtained by the technique of dynamic speckle. The experimental platform used has a CCD camera, a He-Ne laser and a computer for recording and processing information. Experimental results are presented, analysis and development of an automatic control system to validate the proposed medical treatment aimed at reducing the coagulation time of blood